Correspondence of cytological and histopathological diagnoses in diagnostic category V of the Bethesda system: “suspicious for malignancy” - Stanek-Widera, Agata; Biskup-Frużyńska, Magdalena; Śnietura, Mirosław; Zembala-Nożyńska, Ewa; Środa, Maciej; Szczęsny-Karczewska, Weronika; Lange, Dariusz (Polish Journal of Pathology, 2016)
The progress in imaging methods enables fine needle aspiration (FNA) biopsy to be performed on smaller and smaller lesions, including malignant ones (papillary microcarcinomas). The follicular variant predominates in this group, with cytological features often not permitting an unbiased interpretation. The aim of the study was to determine the degree of reliability of the “suspicious for malignancy” (SM) diagnosis in material from the Institute of Oncology in Gliwice (IO). 290 primary SM diagnoses were established from 2010 to 2015 in the IO, including the consultations. None of the patients was treated surgically after the first FNA resulting in diagnostic category V (DC V). After the second FNA 80 patients underwent surgery, after the third 58, and after subsequent FNA 10. Together, 148 surgical resections were performed. Among 148 patients treated surgically, 111 were diagnosed with malignant lesions, which constitutes 75%. Predominantly – in 91 cases – the histopathological outcome was papillary carcinoma. The others were: 16 medullary carcinomas, 2 follicular carcinomas, and 2 poorly differentiated carcinoma cases. Moreover, 8 follicular adenomas and 28 nonneoplastic lesions were found. The high positive predictive value (PPV = 75%) of SM diagnosis established in the IO testifies to the high reliability of this test. Diagnostic category V in FNA should be an indication for surgical treatment.